Implementation of Lean Management to Improve Hospital Pharmacy Performance in Indonesia - Mufida, Ifa; Amalia Rizki, Nurul; Holipah (Jurnal Ilmiah Administrasi Publik, 2025)
Hospital pharmaceutical supplies account for 40% to 50% of total hospital revenue.High quality pharmaceutical services in hospitals can be used as quality and cost controls in hospital performance assessment.  The lean concept is one of the hospital management approaches to provide high-quality services. How is lean implemented in pharmacy installation? Based on this literature study, it was found that the most common waste in outpatient pharmacies was waiting, followed by overprocessing, defects, and motion. In inpatient pharmacy, the dominant wastes are defects and waiting. Lean tool interventions that can be used in this case include value stream mapping (VSM), 5S, spaghetti diagrams, and kanban. Some studies also recommend taking into account the number of human resources in pharmacy services and optimizing the use of SIM-RS. Kaizen in the hospital service process can be done by creating a PDSA cycle. This study concluded that lean management can improve the performance of outpatient pharmacy installations in hospitals in Indonesia. However, the exact effect of lean management on inpatient pharmacy installations is unknown due to limited literature sources.